KONTRUKSI HUKUM SYARIAH TERHADAP FENOMENA PAY-WHAT-YOU-WANT (BAYAR SEIKLASNYA) DALAM STRATEGI PEMASARAN MODERN - Muhammad Sauqi; Siliwangi Siliwangi; Ridho Saputra; Muhammad Zainuri (TAKAFUL : Jurnal Ekonomi Dan Perbankan Syariah, 2026)
The development of marketing strategies in the modern economy has given rise to various innovative pricing models, one of which is the Pay-What-You-Want (PWYW) system, or the “pay as you wish” payment model. This model allows consumers the freedom to determine the amount they consider appropriate for a product or service. Although this strategy is considered capable of increasing consumer trust and loyalty, its existence raises normative questions from the perspective of Islamic economic law, particularly regarding the clarity of price within a sale and purchase contract. This study aims to analyze the construction of Islamic law toward the practice of Pay-What-You-Want in the context of modern marketing strategies and to assess its compatibility with the principles of fiqh muamalah. This research uses a qualitative approach with a library research method through the analysis of literature on fiqh muamalah, contemporary Islamic economics, and academic studies related to the Pay-What-You-Want model in modern business practices. The analysis is conducted using a normative-conceptual approach that examines the principles of contracts (akad), price clarity (tsaman), mutual consent of the parties (an-tarāḍin), and the potential presence of gharar (uncertainty) in transactions. The results of the study indicate that the Pay-What-You-Want practice can, in principle, be understood as a form of flexibility in the pricing mechanism as long as it fulfills the element of mutual consent and does not create uncertainty that harms either party. From the perspective of Islamic law, this model may be constructed as a permissible form of transaction provided that it fulfills the principles of transparency, fairness, and does not contain excessive gharar. Therefore, the Pay-What-You-Want practice can be viewed as a marketing innovation compatible with the principles of Islamic economics when implemented within the framework of Sharia business ethics.